The Execution of Burning of Seized Narcotics Goods in Open Space on Environmental Health from a Rights Perspective - Gazhy Diemas Prahadi; Erika Magdalena Chandra; Ajie Ramdan (Journal of Law, Politic and Humanities, 2025)
In the verdict of a narcotics case, the destruction of confiscated narcotics is usually one of the rulings that must be implemented. In Indonesia, the method of destroying confiscated narcotics goods that is commonly used in the execution of decisions in the form of destroying confiscated narcotics goods is by using the open burning method. However, this method of burning confiscated goods is considered to potentially violate human rights because it affects the environment and public health. This research aims to find out how human rights views on the open burning of confiscated narcotics and to determine the destruction procedure that is in accordance with human rights standards in Indonesia. The research method used in this research is socio-legal by using descriptive analytical research specifications. The research stages were carried out with secondary data library research and field research in the form of interviews with the National Narcotics Agency. Based on the results of the research, it can be concluded that the method of burning confiscated narcotics in open spaces can violate human rights. This is because the smoke from the combustion still contains high levels of dangerous narcotic substances, thus violating the right to a clean, healthy and sustainable environment. Furthermore, regarding the method of destroying confiscated narcotics that is safe for the environment and the surrounding community, namely using an incinerator. This is because incinerators do not produce smoke from combustion, so they do not pollute the environment and are not harmful to the surrounding community